The Effect of Yttrium Oxide Reinforcement on the Microstructural and Mechanical Properties of Biologically Derived Hydroxyapatite - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2015)
In the present study, hydroxyapatite used as a matrix material was derived from the femur bones of Meleagris gallapova (MGHA) and then reinforced with yttriyum oxide (Y2O3, 5 and 10 wt.%). Then samples pelleted at 350 MPa were sintered between 900 and 1300 degrees C. Finally, the effect of Y2O3 reinforcement on the microstructural and mechanical properties of MGHA was investigated. Scanning electron microscope (SEM) and X-ray diffraction (XRD) patterns were used for microstructural examinations. Density, microhardness and compressive strengths of composites were used to analyze their mechanical properties. Experimental results show that mechanical properties of composites were enhanced by increasing the temperature. The optimum results were obtained for MGHA-10% Y2O3 composites sintered at 1200 degrees C.
Keywords: COMPOSITES